Role of HLA-DP and HLA-DQ on the clearance of hepatitis B virus and the risk of chronic infection in a multiethnic population - Trinks, Julieta (2017)
Background & Aims: HBV infection exhibits geographical variation in its distribution in South America. While HBV rates are low in central Argentina, the north-western region exhibits intermediate HBV rates. Unfortunately, the reasons that could explain this difference are still unknown. Methods: a total of 1440 Argentines were recruited and grouped into HBV patients, HBV-resolved individuals and healthy controls. Genetic ancestry was assessed by analysis of biparental lineages and ancestry autosomal typing. SNPs of HLA-DPA1 (rs3077), HLA-DPB1 (rs9277542), HLA-DQB1 (rs2856718) and HLA-DQB2 (rs7453920) were determined, and HBV genotyping was performed by phylogenetic analysis in HBV patients. Results: Native American ancestry prevailed in the north-western region when compared with central Argentina (P<.0001). However, no differences were observed among the three groups of each region. The distribution of HBV genotypes revealed significant differences (P<.0001). Three SNPs (rs3077, rs9277542 and rs7453920) showed a significant association with protection against chronic HBV and viral clearance in both regions. The remaining SNP showed a significant association with susceptibility to chronic HBV. The frequency rates of rs3077-T, related to protection against chronic HBV and viral clearance, were lower in north-western Argentina when compared with central Argentina. The same uneven frequency rates were observed for SNP rs9277542. Conclusions: this is the first study addressing the associations between the HLA-DP and HLA-DQ loci and the protection against chronic HBV and viral clearance in a multiethnic South American population. The uneven distribution of HLA-DP and HLA-DQ supports the HBV epidemiological differences observed in these two regions of Argentina with dissimilar ancestry genetic background.